(untitled) (Fiep Bulletin - online, 2012)
Introduction: Patients with chronic kidney disease (CKD) have reduced exercise tolerance compared to healthy subjects, which complicates the implementation of activities of daily living. The reasons for this reduction are not fully elucidated. Objective: Therefore, we assessed the exercise capacity of patients with CKD treated at the physiotherapy clinic of the Union. Methods: Patients tested for exercise capacity, the Shuttle Walk Test, before and after 6 months of treatment. For the test patients were instructed to walk for 10 meters, surrounding two cones, as long as possible, increasing speeds, under the guidance of a sound signal and stopped by intolerance to maximum effort. Before and after the test, were measured blood pressure, heart rate and breathing, and was valued at the lower limbs and dyspnea according to Borg scale and the test was done during cardiac monitoring. Results: The sample comprised 14 patients, 8 men and 6 women, mean age 51.7 ± 0.7 years. Before treatment the average distance traveled, was 339.2 ± 1.9 meters and after treatment, the average was 382.8 ± 141 meters, an increase of 11%, which was statistically significant (p <0 , 02). The patients had very low exercise capacity before treatment was 12.6 ± 2.8 ml / kg / min and after 13.7 ± 3.5 ml / kg / min, which was statistically significant (p <0.02 ). Conclusion: We conclude that 6 months of treatment increased exercise tolerance, promoting improved quality of life and preventing the progression of the lesions.